2003
DOI: 10.1002/anie.200351541
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Organized Calcium Carbonate with Regular Surface‐Relief Structures

Abstract: CaCO3 composites with regular surface‐relief structures have been synthesized (see picture). These sub‐micrometer‐scale structures are spontaneously formed on a thin matrix of a modified polysaccharide from aqueous solution containing an acidic polymer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
125
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(130 citation statements)
references
References 43 publications
5
125
0
Order By: Relevance
“…Detailed analyses of the biological processes have allowed us to use or mimic them for creating a new generation of synthetic materials (Sugawara et al 2003;Nuraje et al 2006;Sano et al 2006). The Mms6 represents a class of proteins that are tightly associated with the BacMP surface in M. magneticum AMB-1 .…”
Section: In Vitro Chemical Synthesis Of Magnetite Particlesmentioning
confidence: 99%
“…Detailed analyses of the biological processes have allowed us to use or mimic them for creating a new generation of synthetic materials (Sugawara et al 2003;Nuraje et al 2006;Sano et al 2006). The Mms6 represents a class of proteins that are tightly associated with the BacMP surface in M. magneticum AMB-1 .…”
Section: In Vitro Chemical Synthesis Of Magnetite Particlesmentioning
confidence: 99%
“…It has been demonstrated that various synthetic complexes including macromolecules such as poly (acrylate), poly (Glu) or poly (Asp), stearic acid monolayer, glycoproteins, and mercaptophenol-protected gold colloids have specific and prominent influences on mediating the formation of ACC [8][9][10]. Aizenberg et al previously suggested that the ACC film crystallization process occurs by mass transport between the amorphous and crystalline [11].…”
Section: ____________________mentioning
confidence: 98%
“…The formation of CaCO 3 films on an insoluble organic substrate in the presence of PAA has been investigated by many researchers. [9][10][11][91][92][93] However, the influence of the polyelectrolyte on the morphology of CaCO 3 crystals has not been sufficiently clarified because morphological evolution required the coexistence of the organic substrates in most of the previous studies. We systematically investigated the influence of the concentration and the molecular weight of PAA on the morphological evolution of CaCO 3 grown on a simple glass substrate in order to clarify the performance of the polymeric molecules.…”
Section: Emergence Of Self-organizationmentioning
confidence: 99%
“…4 Thus, biomimetic approaches for crystal growth has been studied using various kinds of organic molecules and molecular assembly. [5][6][7][8][9][10][11][12][13][14][15] Morphogenesis with coexisting molecules has been reported by many research groups as well as the control of the nucleation sites with specific organic surfaces, including polymer films and self-assembled monolayers. Emergence of complex and hierarchical architectures of inorganic crystals through self-organization has been found in aqueous solution systems.…”
Section: Introductionmentioning
confidence: 99%